The Flame and the Breeze: Life and Longevity Practices in Three Bengali Sufi Texts from the Long Seventeenth Century - Mukharji, Projit Bihari (History of Science in South Asia, 2017)
This is a preliminary report on the longevity practices discussed in a Bengali Islamic Yogic text by Haji Muhammad called Nurjamal ba Suratnama written in the last decade of the sixteenth century. This and other similar texts were authored by Bengali literati in the kingdom of Roshang that encompassed at the time both the Arakan and eastern Bengal. I first present the unique cultural and political context in which these texts were produced. Next I discuss the particular text and its author. In doing this I also review the scant scholarship that exists on the material as well as advancing a different and parallel analytic strategy by which the texts might, in my view, be opened up to a broader range of inquiries. In the two subsequent sections I use the proposed strategy of 'figural history' to interrogate two different figures of 'life' that are found in the text under investigation. The entire discussion of longevity practices is organized around these figures of life and I suggest that they need to be explored more fully in their individuality. The conclusion pulls the strings together and reiterates the case for studying the longevity practices in this and other similar texts using figural history as an analytic strategy.